2019
DOI: 10.1090/proc/14495
|View full text |Cite
|
Sign up to set email alerts
|

Mixed weak estimates of Sawyer type for generalized maximal operators

Abstract: We study mixed weak estimates of Sawyer type for maximal operators associated to the family of Young functions Φ(t) = t r (1 + log + t) δ , where r ≥ 1 and δ ≥ 0. More precisely, if u and v r are A1 weights, and w is defined as w = 1/Φ(v −1 ) then the following estimateholds for every positive t. This extends mixed estimates to a wider class of maximal operators, since when we put r = 1 and δ = 0 we recover a previous result for the classical Hardy-Littlewood maximal operator. This inequality generalizes the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…That conjecture was positively answered recently in [24] where several quantitative estimates were provided as well. At this point we would like to mention, as well, a recent generalization provided for Orlicz maximal operators in [2].In [7], besides the aforementioned results, it was shown that (1.1) holds if u ∈ A 1 and v ∈ A ∞ (u) (see Section 2.2 for the precise definition of A p (u)). The advantage of that condition is that the product uv is an A ∞ weight.…”
mentioning
confidence: 88%
“…That conjecture was positively answered recently in [24] where several quantitative estimates were provided as well. At this point we would like to mention, as well, a recent generalization provided for Orlicz maximal operators in [2].In [7], besides the aforementioned results, it was shown that (1.1) holds if u ∈ A 1 and v ∈ A ∞ (u) (see Section 2.2 for the precise definition of A p (u)). The advantage of that condition is that the product uv is an A ∞ weight.…”
mentioning
confidence: 88%
“…Later on, in [4] the author showed that a similar behavior occurs in the case u,vrA1, that is, uw{}xdouble-struckRn:MΦ0false(fvfalse)false(xfalse)v(x)>tCRnnormalΦ0false|ffalse(xfalse)false|vfalse(xfalse)tufalse(xfalse)dx,where w and Φ 0 are as above.…”
Section: Introductionmentioning
confidence: 85%
“…A motivation for studying these type of estimates is to find an alternative way to prove the boundedness of the operator MΦ. In [4] was established that (1.4) extends the estimates in [6] not only for M but also for Mr. However, this inequality turns out to be non‐homogeneous, and even when vrA1, the resulting weight w might not.…”
Section: Introductionmentioning
confidence: 99%
“…holds for every positive t, where w = 1/Φ 0 (v −1 ), Φ 0 (t) = t r (1 + log + t) δ , with r ≥ 1 and δ ≥ 0. Later on, in [3] the author showed that a similar behavior occurs in the case u, v r ∈ A 1 , that is,…”
Section: Introductionmentioning
confidence: 80%